2009
DOI: 10.1007/s10290-009-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Specialization, outsourcing and wages

Abstract: This paper studies the impact of outsourcing on individual wages. In contrast to the standard approach in the literature, we focus on domestic outsourcing as well as foreign outsourcing. We argue that if outsourcing is associated with specialization gains arising from an increase in the division of labor, domestic outsourcing tends to increase wages for both unskilled and skilled labor. We use a panel data set of workers in Danish manufacturing industries to show that domestic and foreign outsourcing affect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 18 publications
5
37
0
2
Order By: Relevance
“…To assess the impact of outsourcing on individual wages we follow the approach in Geishecker and Görg (2008) and Munch and Skaksen (2009) and estimate simple Mincer human capital wage equations of the form Source: Nickell et al (2005) log…”
Section: Methodsmentioning
confidence: 99%
“…To assess the impact of outsourcing on individual wages we follow the approach in Geishecker and Görg (2008) and Munch and Skaksen (2009) and estimate simple Mincer human capital wage equations of the form Source: Nickell et al (2005) log…”
Section: Methodsmentioning
confidence: 99%
“…Following Feenstra and Hanson (1999), several works have studied how foreign outsourcing, evaluated through direct or indirect measurements of imported intermediate inputs, affect labour demand (see e.g. Hijzen et al 2005, Ekholm and Hakkala 2005, or Munch and Skaksen 2009. The results are mixed but point in several cases to a significant impact of outsourcing upon labour demand.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was supported by the significant research conducted by McKinsey and Company (2004) as well as Munch and Skaksen (2005). Burhany (2009) found that outsourcing and core competency strategies have affected firm financial performance of the manufacturing companies in Indonesia.…”
Section: Introductionmentioning
confidence: 52%
“…On the other hand, the lowest value of weighted rating (0.5441) is Row 1 with government regulations on outsourcing (KP). Munch and Skaksen (2005) identify that wage and skill of worker can affect outsourcing decision. Kremic, Tukel and Rom (2006) identify factors that support outsourcing decision are cost of production, business environment, business strategy, and business characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation